Spatial and temporal dynamics of anthropogenic threats on the biodiversity of Virunga National Park - Thasi, Kakule; Martin, Tchamba; Gueguim, Daden (International Journal of Forest, Animal and Fisheries Research, 2021)
The Protected Area (PA) Network of the Democratic Republic of Congo represents 13% of the national area known for its rich biodiversity, but highly threatened. Virunga National Park (PNVi) one of these most important protected areas is also plagued by irrational use. The aim of this study is to analyze the spatial-temporal dynamics of threats to the biodiversity of PNVi. Two satellite images were used including landsat 2TM February 1980 and landsat 8 OLI February 2020 and documentary technique. As a result plant formations and wildlife have suffered a very considerable decline. The tree savannah reduced from 14.7% in 1980 to 8.9% in 2020. The loss of wildlife in Virunga National is worrying for hippos, buffaloes and elephants between 1981 and 2017.A small reconstruction of hippos between 2003 and 2006 and 2013. The annual loss rate of wildlife is very high for buffalo (7.8%), followed by hippos (6.7%) elephants (3%). Gorillas have suffered a relatively small loss over the past 4 decades (annual loss rate of 0.04%). All of these results are a response to the hypothesis that over the past forty years the anthropogenic threats to the biodiversity of PNVi have intensified in space and over time, three-fourths of the park has been destroyed, wildlife biodiversity has been halved including hippos, elephants, gorillas and buffaloes.